Phenotypic and Genotypic Characterization of Some Virulence Factors among Proteus mirabilis Isolated from Clinical Samples in Al-Najaf Al-Ashraf/ Iraq - Ahlam Kadhum Al-Yasseen (Journal of Global Pharma Technology, 2016)
The present study aimed to investigate the phenotypic and genotypic pattern of some virulence factors in Proteus mirabilis isolates from clinical samples. A total of 110 urine samples were collected from patients with urinary tract infection from both sexes and 100 vaginal swabs were collected of women with vaginal infections during the period from October 2017 to January 2018. The results of primary isolation and identification of bacterial isolates depending on microscopic, culturing on CHROM agar and biochemical test showed that 36.3% of isolates were belong to Proteus while the results of PCR techniques that used to confirmed identification using 16SrRNA revealed that 27.2% of isolates were belong to Proteus mirabilis. Variable results in the ability of bacterial isolates to produce protease and hemolysin have been obtained in which 30% and 100% of bacterial isolates gave positive results respectively. Also the results of PCR technique showed that all isolates (100%) were possess zap A, rsb A and mrp A encoding for the production of protease, protein that regulates  bacterial swarming behavior and mannose resistant pilli (MR /P) respectively by the appearance of amplicons with molecular weight  552, 485 and 366 bp.Keywords:  Genotypic; Proteus mirabilis; Phenotypic; and Clinical Samples.